Association of Pasteurella multocida Toxin with Vimentin - Shime, Hiroaki (American Society for Microbiology, 2002)
To help understand the molecular mechanisms of Pasteurella multocida toxin (PMT) action, we searched for a cellular protein interacting with PMT. The ligand overlay assay revealed a 60-kDa cellular protein that binds to a region from the 840th to 985th amino acids of the toxin. This protein was identified as vimentin by peptide mass fingerprinting. The N-terminal head domain of vimentin was further found to be responsible for the binding to the toxin.